Is folic acid safe for non–muscle-invasive bladder cancer patients? An evidence-based cohort study - Tu, Huakang (Am J Clin Nutr, 2018)
BACKGROUND: Patients with cancer are highly concerned about food choices and dietary supplements that may affect their treatment outcomes. Excess folic acid (synthetic folate) from supplements or fortification can lead to accumulation of unmetabolized folic acid in the systemic circulation and urine and may promote cancer growth, especially among those with neoplastic alterations. OBJECTIVE: We investigated the prospective association between synthetic compared with natural folate intake and clinical outcomes in non–muscle-invasive bladder cancer (NMIBC), which is a highly recurrent disease. DESIGN: In a cohort of 619 NMIBC patients, folate intake at diagnosis was assessed with a previously validated food-frequency questionnaire and categorized according to tertiles. After a median follow-up of 5.2 y, 303 tumor recurrence and 108 progression events were documented from medical record review. Multivariable Cox proportional hazards and logistic models were used to estimate adjusted HRs and ORs with 95% CIs. RESULTS: Synthetic folic acid intake was positively associated with a risk of recurrence among NMIBC patients (medium compared with low intake—HR: 1.72; 95% CI: 1.20, 2.48; P = 0.003; high compared with low intake—HR: 1.80; 95% CI: 1.14, 2.84; P = 0.01). Patients with a higher folic acid intake were more likely to have multifocal tumors at diagnosis (medium or high compared with low—OR: 2.08; 95% CI: 1.08, 4.02; P = 0.03). In contrast, natural folate intake tended to be inversely associated with the risk of progression (medium or high compared with low—HR: 0.68; 95% CI: 0.44, 1.04; P = 0.08). CONCLUSIONS: A high intake of synthetic folic acid, in contrast to the natural forms, is associated with an increased risk of recurrence in NMIBC and multifocal tumors at diagnosis, which suggests that folic acid may be unsafe for NMIBC patients. These findings provide some evidence for nutritional consultation with regard to folate intake among NMIBC patients.